Self-Efficacy Of Teachers In Special Education - Malik, Munawar; Qureshi, Maria; Bano, Humara (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Self-efficacy is one’s belief or perception about one’s professional traits. Likewise, a teacher’s efficacy is a  teacher’s belief about his competencies required to develop  desirable change in learner’s behavior. Studies have identified  teacher efficacy as one of the distinct variables that  potentially can differentiate among teachers and  corresponding work behaviors. Teaching children with special  needs demands some exceptional traits and skills on the part  of the teacher when compared to a teacher of regular education system. A special education teacher is a  professional responsible for providing educational support  and intervention for students with exceptional needs. The  study aims to identify the self efficacy of teachers serving in  schools for children with hearing impairment in special  education institutions through a descriptive research i.e. cross  sectional survey. Identified variables of self efficacy were  planning, instruction, class management and evaluation. Other  objectives were to identify relationship of self efficacy with  educational qualification of teachers, gender, age and respective experiences. The population comprised teachers of  Sp. Ed. schools in district Punjab. Purposive, random  convenient sampling technique was used to select 100  teachers as a sample. The tool comprised a questionnaire with  30 items duly validated and piloted before formal data  collection. Findings include a higher level of self efficacy  among teachers in the domains of planning, instruction, class  management and evaluation. A strong relationship has been  identified among self efficacy of teachers, their respective  age, gender, qualification and experience.
Keywords: Self-Efficacy; Students with Special Needs; Teaching Competencies